If the average of the numbers n sin n ∘ , where n = 2 , 4 , 6 , ⋯ , 1 8 0 is cot x ∘ . Then what is the value of x ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We have S = 9 0 1 n = 1 ∑ 9 0 2 n sin ( 2 n ) ∘ = 9 0 1 n = 1 ∑ 8 9 ( 2 n ) sin ( 2 n ) ∘ = 9 0 1 [ n = 1 ∑ 4 4 ( 2 n ) sin ( 2 n ) ∘ + 9 0 + n = 1 ∑ 4 4 ( 1 8 0 − 2 n ) sin ( 1 8 0 − 2 n ) ∘ ] = 1 + 2 n = 1 ∑ 4 4 sin ( 2 n ) ∘ = 1 + 2 n = 1 ∑ 4 4 sin 9 0 n π = 1 + 2 I m [ n = 1 ∑ 4 4 e 9 0 n π i ] = 1 + 2 I m ( e 9 0 π i − 1 e 2 π i − 1 ) = 1 + 2 sin 1 8 0 π sin 4 π sin ( 4 π − 1 8 0 π ) = 1 + sin 1 8 0 π cos 1 8 0 π − cos ( 2 π − 1 8 0 π ) = cot 1 8 0 π = cot 1 ∘ making the answer 1 .
Problem Loading...
Note Loading...
Set Loading...
I'll post a long, detailed solution. Perhaps there's an easier one, I don't know.
Let us consider the sum:
n = 1 ∑ 9 0 cos ( 2 n x )
This is the same as ( j is the imaginary unit):
n = 1 ∑ 9 0 cos ( 2 n x ) = n = 1 ∑ 9 0 ℜ [ e j 2 n x ]
n = 1 ∑ 9 0 cos ( 2 n x ) = ℜ ⎣ ⎡ n = 1 ∑ 9 0 e j 2 n x ⎦ ⎤
By geometric progression sum formula:
n = 1 ∑ 9 0 cos ( 2 n x ) = ℜ [ e j 2 x − 1 e j 1 8 2 x − e j 2 x ]
n = 1 ∑ 9 0 cos ( 2 n x ) = ℜ [ ( e j 2 x − 1 ) ⋅ ( e − j 2 x − 1 ) ( e j 1 8 2 x − e j 2 x ) ⋅ ( e − j 2 x − 1 ) ]
n = 1 ∑ 9 0 cos ( 2 n x ) = ℜ [ 2 − 2 cos ( 2 x ) e j 1 8 0 x − e j 1 8 2 x − 1 + e j 2 x ]
n = 1 ∑ 9 0 cos ( 2 n x ) = 2 − 2 cos ( 2 x ) cos ( 1 8 0 x ) − cos ( 1 8 2 x ) − 1 + cos ( 2 x )
Since cos ( 2 x ) = 1 − 2 sin 2 ( x ) :
n = 1 ∑ 9 0 cos ( 2 n x ) = 4 sin 2 ( x ) cos ( 1 8 0 x ) − cos ( 1 8 2 x ) − 1 + cos ( 2 x )
Differentiating on both sides with respect to x :
n = 1 ∑ 9 0 − 2 n sin ( 2 n x ) = 1 6 sin 4 ( x ) [ − 1 8 0 sin ( 1 8 0 x ) + 1 8 2 sin ( 1 8 2 x ) − 2 sin ( 2 x ) ] ⋅ [ 4 sin 2 ( x ) ] − [ cos ( 1 8 0 x ) − cos ( 1 8 2 x ) − 1 + cos ( 2 x ) ] ⋅ [ 4 sin ( 2 x ) ]
Make x = 1 o and considering that cos ( 1 8 0 o + x o ) = − cos ( x o ) and sin ( 1 8 0 o + x o ) = − sin ( x o ) :
n = 1 ∑ 9 0 − 2 n sin ( 2 n o ) = 1 6 sin 4 ( 1 o ) ( − 1 8 4 sin ( 2 o ) ) ( 4 sin 2 ( 1 o ) ) − ( 2 cos ( 2 o ) − 2 ) ( 4 sin ( 2 o ) )
Recalling again that cos ( 2 o ) = 1 − 2 sin 2 ( 1 o ) :
n = 1 ∑ 9 0 2 n sin ( 2 n o ) = 1 6 sin 4 ( 1 o ) ( 1 8 4 sin ( 2 o ) ) ( 4 sin 2 ( 1 o ) ) + ( − 4 sin 2 ( 1 o ) ) ( 4 sin ( 2 o ) )
Dividing above and below by 4 sin 2 ( 1 o ) :
n = 1 ∑ 9 0 2 n sin ( 2 n o ) = 4 sin 2 ( 1 o ) 1 8 4 sin ( 2 o ) − 4 sin ( 2 o )
n = 1 ∑ 9 0 2 n sin ( 2 n o ) = 4 sin 2 ( 1 o ) 1 8 0 sin ( 2 o )
Since sin ( 2 o ) = 2 sin ( 1 o ) cos ( 1 o ) :
n = 1 ∑ 9 0 2 n sin ( 2 n o ) = 4 sin 2 ( 1 o ) 3 6 0 sin ( 1 o ) cos ( 1 o )
n = 1 ∑ 9 0 2 n sin ( 2 n o ) = sin ( 1 o ) 9 0 cos ( 1 o )
n = 1 ∑ 9 0 2 n sin ( 2 n o ) = 9 0 cot ( 1 o )
9 0 1 n = 1 ∑ 9 0 2 n sin ( 2 n o ) = cot ( 1 o )
Which is the average we are looking for. Thus:
x = 1